2020
DOI: 10.1093/jas/skaa292
|View full text |Cite
|
Sign up to set email alerts
|

Practical application of an impractical bovine genotype: creating bilateral twin pregnancies in Trio allele carriers

Abstract: Bovine twin birth is associated with detriments including increased embryo/fetal losses, malpresentation and dystocia. Incidence of these is lessened in bilateral compared to unilateral twin pregnancy. This study was undertaken to assess use of follicular ablation by aspiration to create bilateral twin pregnancies in females with genetic potential for ~3.5 ovulations per cycle (Trio allele carriers). In Experiment 1, carriers (n=30) and non-carriers (n=10) were synchronized for ovulation and timed artificial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Future studies may focus on reducing DOV through increasing circulating P4 during preovulatory follicle development using protocols such as Double-Ovsynch (Cunha et al, 2008;Wiltbank et al, 2012;Martins et al, 2018), genetic selection for reduced twinning or DOV (Lett and Kirkpatrick, 2018), aspiration of codominant follicles to increase likelihood of SOV (López-Gatius and Garcia-Ispierto, 2020), or use of embryo reduction (Hanrahan, 1983;Andreu-Vázquez et al, 2012b;. In regard to follicle aspiration, we have recently demonstrated that follicle aspiration can be used to reduce number of DF and ensure ovulation of a single DF in each ovary to increase bilateral twinning rates in beef cattle that are carriers for the high fecundity Trio allele (Madureira et al, 2020). Future hormonal methods, based on a thorough understanding of the endocrine basis for DOV, may be developed to practically optimize reproductive efficiency through manipulation of ovulation rate.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may focus on reducing DOV through increasing circulating P4 during preovulatory follicle development using protocols such as Double-Ovsynch (Cunha et al, 2008;Wiltbank et al, 2012;Martins et al, 2018), genetic selection for reduced twinning or DOV (Lett and Kirkpatrick, 2018), aspiration of codominant follicles to increase likelihood of SOV (López-Gatius and Garcia-Ispierto, 2020), or use of embryo reduction (Hanrahan, 1983;Andreu-Vázquez et al, 2012b;. In regard to follicle aspiration, we have recently demonstrated that follicle aspiration can be used to reduce number of DF and ensure ovulation of a single DF in each ovary to increase bilateral twinning rates in beef cattle that are carriers for the high fecundity Trio allele (Madureira et al, 2020). Future hormonal methods, based on a thorough understanding of the endocrine basis for DOV, may be developed to practically optimize reproductive efficiency through manipulation of ovulation rate.…”
Section: Discussionmentioning
confidence: 99%
“…A total of eight twin sets (16 cattle) were used in this study, and all were of Angus‐crossbred type. Twin sets 1–4 (calf ID numbers G001–G008) were produced by a project studying the creation of bilateral twin pregnancies in females with a high ovulation rate genotype (Madureira et al, 2020). Twin sets 5–8 (calf ID numbers G013, G014, G020, G021, G070, G071, G080 and G081) occurred naturally in the Lancaster herd.…”
Section: Figurementioning
confidence: 99%